Maternal Trauma and Children's Functioning: The Role of Kinship Social Support. Issue 4 (20th April 2016) - Krauss, Lily A.; Wilson, Christina K.; Padrón, Elena; Samuelson, Kristin W.
ABSTRACT: Although research has documented the detrimental effects of maternal trauma on child behavior (Lambert, Holzer, & Hasbun, 2014), the role of extended family support in potentially mitigating the effects of intergenerational transmission of trauma is not clearly understood. With a diverse community sample of 52 trauma-exposed mothers and their children between the ages of 7 and 12, we investigated relationships between kinship social support, maternal trauma exposure severity, maternal posttraumatic stress disorder (PTSD) symptom severity, and child behavioral problems. Results showed that kinship social support was negatively related to maternal trauma exposure severity, maternal PTSD symptom severity, child internalizing behaviors, and child externalizing behaviors. Additionally, kinship social support moderated the relationship between maternal trauma exposure severity and child internalizing behaviors. These results have implications in the implementation of interventions aimed at supporting diverse families facing trauma that incorporate extended family networks.